The Science, Technology, Society and Environment (STSE) Approach: Perceptions of Secondary School Science Students (Journal of Social Sciences Review, 2022)
The major purpose of this study was to investigate the perceptions of government secondary school science students towards Science, Technology, Society and Environment (STSE) approach in district Dir Lower. The quantitative (survey) design was used. The data were collected from 737 science students through a self-developed questionnaire based on multiple scales. The respondents consisted of both boys and girls science students of secondary and higher secondary schools. The questionnaire included questions about awareness of STSE approach and the problems impeding this approach in science teaching. The reliability of the questionnaire was established through Cronbach's alpha and found 0.87. Data were analyzed by using frequency, percentage, mean, and standard deviation (Descriptive Statistics).  The result of the study revealed that students were familiar with this approach and considered it helpful to enhance the critical and scientific thinking skills of students as it leads to motivate them in learning the abstract concepts of science. The study recommended that science teachers may be given proper training to implement this approach in the classroom to teach science subjects effectively.
Keywords: STSE approach; Science Students; Critical skills; Scientific Skills